Performance of Pekin ducks in smallholdings under different rearing systems - Engku Azahan (2013)
Ducks raised under the intensive systems of raised floor housing showed growth responses comparable to those of birds reared semi-intensively with the provision of a pool of water for swimming. Differences in the mean values of all the carcass traits examined were not significant between the two treatments. It was concluded that the intensive full-confinement rearing system, similar to that used for chickens, could be adopted for growing Pekin ducks in smallholdings without bringing any adverse effect to the birds